2001
DOI: 10.2337/diabetes.50.9.2133
|View full text |Cite
|
Sign up to set email alerts
|

Depressed Levels of Ca2+-Cycling Proteins May Underlie Sarcoplasmic Reticulum Dysfunction in the Diabetic Heart

Abstract: In view of the depressed sarcoplasmic reticulum (SR) Ca 2؉-pump and Ca 2؉ -release activities in the diabetic heart and the critical role of phosphorylation in regulating the SR function, we examined the status of Ca -pump ATPase, and phospholamban. On the other hand, the CaMK-and PKA-mediated phosphorylations of these Ca 2؉ -cycling proteins, the endogenous SR CaMK and PKA activities, and the endogenous SR and cytosolic phosphatase activities were increased in the diabetic heart. Treatment of 3-week diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
0
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 35 publications
7
87
0
4
Order By: Relevance
“…The protein content of SR Ca 2ϩ -cycling proteins SERCA2a and PLB and its phosphorylated forms, serine-16 PLB and threonine-17 PLB, were determined by Western blot analysis as described previously (27,28,40). SR samples (20 g) were separated by SDS-polyacrylamide gel electrophoresis on 10% (for SERCA2a) and 15% (for PLB, serine-16 PLB, and threonine-17 PLB) gels and transferred to polyvinylidene difluoride membranes.…”
Section: Inset)mentioning
confidence: 99%
“…The protein content of SR Ca 2ϩ -cycling proteins SERCA2a and PLB and its phosphorylated forms, serine-16 PLB and threonine-17 PLB, were determined by Western blot analysis as described previously (27,28,40). SR samples (20 g) were separated by SDS-polyacrylamide gel electrophoresis on 10% (for SERCA2a) and 15% (for PLB, serine-16 PLB, and threonine-17 PLB) gels and transferred to polyvinylidene difluoride membranes.…”
Section: Inset)mentioning
confidence: 99%
“…Accordingly the attenuation of arrhythmias in late stage of diabetes may be related to a reduction in CaM KII activity. However, some of our earlier observations (18,37) have reported that although SR CaM KII activity is increased in the diabetic (6-wks post STZ-induced diabetes) heart, it is decreased in 10 wks sucrose-fed rats (38). Therefore, it appears that changes in CaM KII activity are biphasic in nature and dependent on the stage or severity of diabetes.…”
Section: Dose Of Epimentioning
confidence: 87%
“…MHCs are contractile proteins and the shift from the adult isoform (MHCα) toward a fetal isoform (MHCβ) is implicated in cardiac dysfunction (33). The decreased expression of SERCA2 is also related to cardiac dysfunction because of dysregulation of Ca 2+ handling in the myoplasm (34). Rivoglitazone had no effects on the expression levels of MHCs and SERCA2.…”
Section: Discussionmentioning
confidence: 99%